BIOECOLOGICAL FEATURES OF GROUND BEETLES OF GUMBETOVSKY DISTRICT OF DAGHESTAN REPUBLIC - G. M. NAKHIBASHEVA; R. Kh. MAGOMEDBEKOV; G. M. MUKHTAROVA; Sh. G. ABDURAKHMANOV (Юг России: экология, развитие)
Ground beetles of the Gumbetovskiy area are studied. For the first time for the territory there are defined 95 species of the beetles related to 28 genus. Bioecological features of the species are presented and the analysis of the received materials is lead.